Pengaruh Financial Knowledge terhadap Financial Behavior Dimediasi oleh Locus of Control dan Financial Self Efficacy pada UMKM Kabupaten Karo - Surbakti, Dona Doni; Muslih, Muslih (https://jurnal.binamandiri.ac.id/, 2024)
This research investigates how financial knowledge, locus of control, and self-efficacy influence financial behavior in MSMEs in Karo Regency. Using quantitative analysis, this research tested 100 participants selected through purposive sampling. Applying the PLS-SEM approach with SmartPLS, this research consists of outer model analysis, inner model analysis, and hypothesis testing. The findings highlight the significant impact of financial knowledge, locus of control, and self-efficacy on financial behavior. Financial knowledge directly influences locus of control and self-efficacy. At the same time, the last two factors act as mediators in the relationship between financial knowledge and financial behavior in MSMEs in Karo Regency.